Efektifitas Pelatihan “Pola Asuh Remaja” Untuk Ibu-Ibu Rumah Tangga Berdasarkan Tingkat Pendidikan (Pemahaman Pola Asuh Pada Ibu Rumah Tangga) - Salis Khoiriyati (Nidhomul Haq : Jurnal Manajemen Pendidikan Islam, 2017)
This study aims to examine the effectiveness of training on "Adolescent Care Patterns" on improving understanding of youth parenting patterns. The research was conducted on 7 mothers who had never been educated, 6 mothers who had been educated up to elementary school (SD), and 9 mothers who had been educated to junior high school (SMP). This research uses Quasi Experimental, with design of Group One Pretest-Posttest Design also called before-after design. The result of data analysis using Kruskal Wallis shows that giving training on "Patterns of Younger Children" can improve the understanding of assisted mothers who have never been educated about teenage parenting (Asymp Sig. (2-tailed) Scale of understanding of youth parenting = 0,000 , Where p> 0.05), in assisted mothers who have gone to elementary school (SD) education can also improve understanding of adolescent parenting (Asymp Sig. (2-tailed) Scale of understanding of youth parenting = 0,000 , Where p> 0,05), whereas enrolled mothers who had gone to junior high school (SMP) were not effective in improving understanding about adolescent parenting (Asymp Sig. (2-tailed) = 0,000, where p> 0,05). Qualitative analysis conducted on observation and interview data provides descriptive description of the participants' experience during the training is related to the effectiveness of training on "teenage parenting".